Tinjauan Interfaith Studies Dalam Akulturasi Nilai Leadership Suku Sasak Lombok Serta Relevansinya Terhadap Pendidikan Islam - Moh. Zarkani, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to analyze the contribution of Sasak community leadership values in shaping holistic leadership management within Islamic education. Employing a qualitative approach through literature-based analysis, the research explores cultural and religious values embedded in Sasak leadership traditions. The findings reveal that Sasak leadership is characterized by religiosity, deliberation, and social harmony, which provide a strong foundation for leadership practices in Islamic educational institutions. Local traditions such as the Perang Topat at Lingsar Temple illustrate interfaith cooperation between Muslim and Hindu communities, highlighting that Sasak leadership transcends religious boundaries and fosters inclusive social cohesion. Theoretically, these findings contribute to the development of leadership models in Islamic education by integrating local wisdom with Islamic principles, thereby enriching the discourse of educational leadership with an indigenous perspective. The originality of this study lies in its emphasis on the Sasak community as a case of embodied Islamic leadership, which not only reinforces moral and spiritual values but also promotes justice, moderation, and responsiveness to multicultural realities in educational contexts..